Strengthening Character Education In Preventing Bullying Behavior Of Students In Pesantren - Muhamad Arif; Siti Mahmudah Noorhayati (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The finding of a lot of bullying behavior in Islamic boarding schools has become a negative trend. Islamic educational institutions must make complete improvements. The position of Islamic boarding school students as a stronghold of Islamic education should be able to maintain good values and character by providing good examples, one of which is by not committing acts. Bullying. Character formation is not only limited to implementing good character, it will create a consistent culture (istiqomah). The research method uses qualitative with a case study approach, the primary data sources for this research are Islamic boarding school caregivers, heads, educators (council of teachers), Islamic boarding school guidance and counseling teachers, and Islamic boarding school students, with observation, interview and documentation data collection. Yin presented data analysis through pattern matching, explanation, time series analysis, and repeated observations. The research results show the first character education model, through role models/examples from teachers or Islamic boarding school administrators, the creation of a violence prevention action task force (TPPK), and individual assistance to the students. Meanwhile, some of the character education implemented for students includes religious character, mutual respect amidst the diverse backgrounds of students, the character of responsibility, fairness, sensitivity to all Islamic boarding school conditions, and strengthening Nasionalisme accompanied by the existence of continuous and consistent strengthening. The findings regarding Infinity character are an option in preventing bullying behavior among students in Islamic boarding schools